Changing climate and the permafrost environment on the Qinghai–Tibet (Xizang) plateau. (18th May 2020) - Zhao, Lin; Zou, Defu; Hu, Guojie; Du, Erji; Pang, Qiangqiang; Xiao, Yao; Li, Ren; Sheng, Yu; Wu, Xiaodong; Sun, Zhe; Wang, Lingxiao; Wang, Chong; et al.
Abstract: Permafrost on the Qinghai–Tibet Plateau (QTP) has undergone degradation as a result of recent climate change. This may alter the thermo‐hydrological processes and unlock soil organic carbon, and thereby affect local hydrological, ecological, and climatic systems. The relationships between permafrost and climate change have received extensive attention, and in this paper we review climate change for permafrost regions of the QTP over the past 30 years. We summarize the current state and changes in permafrost distribution and thickness, ground temperature, and ground ice conditions. We focus on changes in permafrost thermal state and in active‐layer thickness (ALT). Possible future changes in ground temperature and ALT are also discussed. Finally, we discuss the changes in hydrological processes and to ecosystems caused by permafrost degradation. Air temperature and ground temperature in the permafrost regions of the QTP have increased from 1980 to 2018, and the active layer has been thickening at a rate of 19.5 cm per decade. The response of permafrost to climate change is not as fast as in some reports, and permafrost degradation is slower than projected by models that do not account for conditions deep in permafrost.